Perbandingan agama - Indonesia... (Proyek Pembinaan Perguruan Tinggi Agama, 1982)
tr, jil.1, c.1-14/why, c.15-16/isr, c.17/ir, jil.1,c.18-21/tr, jil.1=c.22/en, c.23/en, c.24/en, c.25/stoc1, jil1,c.1-21/stoc7.c.22/stc13,jil.1,c.23